JENIS DAN POPULASI SERANGGA PADA BIBIT TANAMAN JABON MERAH Anthocephalus macrophyllus - Alva Rorong; Betsy A.N. Pinaria; Moulwy F. Dien; Caroulus S. Rante (COCOS, 2014)
ABSTRACTAlva Garry Rorong 080318010. Type and Insect Populations in Plant seeds Jabon Red Anthocephalus macrophyllus. Under the guidance of PINARIA, BAN, as chairman, DEEN, MF and Chain, CS as a member.The experiment was conducted at the Forestry Greenhouse Science Program, Faculty of Agriculture, University of Sam Ratulangi, then continued in the laboratory of Entomology and Plant Pests UNSRAT Faculty of Agriculture. This study was carried out for 4 months ie June to September 2012 This study aims to determine the type and insect populations found in plant seeds Jabon red.Total seed used for this study were 80 seedlings. Planting in polybags done manually which makes the planting hole as deep as 7-10 cm by hand, and then the seeds are planted in the hole until the roots are embedded. This study uses a red seed Jabon 3 months old in the nursery area of the Faculty of Agriculture, University of Sam Ratulangi. One month after the first was in the nursery area, remove the seeds and place it in an open area. Seeds are4placed one by one on a regular basis with a distance of 20 x 30 cm. Insects were collected in a bottle found 70% alcohol for identification. Sampling was conducted in the morning (06:00 to 08:00 hours) and afternoon (Jam 4:00 p.m. to 6:00 p.m.) using insect nets mainly on the type of insect that is active and catching fly directly use an aspirator to the non-flying insects. Insects were collected in bottles containing 70% alcohol to be identified in the laboratory. Observations were made on all samples of plants and sampling was performed five times with intervals of once a week.Insects were found to be separated according to its kind, and then identified. Samples of insects were identified to family level using a library Anonymous, 2011b; Myers., Et al, 2014; Lovett G, 2014.The results showed that insects found in red Jabon plant nursery consists of 4 orders, namely: (1) the Order Hymenoptera (Family Cynipidae, Sphecidae, Formicidae); (2) Order Coleptera (Family Scarabaidae); (3) Order Odonata (Libellulidae Family), and (4) Order Homoptera (Family Aphididae) and Family Pseudococcidae. Average of the highest insect population in a row of 173 Family Aphididae tail, Family Pseudococcidae 88.8 tail, tail 43 Family Formicidae, Family Scarabaeidae 4.4 tails, Family Sphecidae 1 tail, tail 0.6 Family Cynipidae and Family Libellulidae 0, 4 tails.